Daily energy and protein intake in hospitalized patients in department of infectious diseases: a prospective observational study - Pekmezci, Aslı Gizem; Gündoğan, Kürşat; Dizdar, Oguzhan Sıtkı; Alp Meşe, Emine (Progress in Nutrition, 2018)
Aims: Malnutrition is associated with increased hospital mortality and morbidity. The aim of this study is to observe the daily energy and protein intake of hospitalized patients at infectious disease department. Methods: A prospective observational study was performed in the Hospital of Erciyes University Medical School during May and November 2014. Nutritional assessment was performed within 24 hours of admission to the department of infectious diseases using the Nutritional Risk Screening-2002 score (NRS 2002). The energy and protein from dietary intake was calculated for each meal by a dietician. Results: Of the 47 patients in this study, 20 were males (43%) and 27 were females (57%) and their ages ranged from 18 to 88 years (53±18 years). Body weight of patients who had >1000 kcal daily energy deficiency were higher than patients who had normal energy intake and their daily protein intake was significantly low. However, the length of their hospital stay was considerably short. Although the mean values of patients’ daily energy intake displayed an increase in the first three days of their stay, there had been a decline in the following days. Conclusions: Energy and protein intake at hospital is insufficient and routine dietetic assessment should be performed for all patients, so that at-risk patients for malnutrition may be identified and early nutritional intervention may be instituted during hospitalization. Patients with more body weight experienced more energy and protein deficiencies during their hospital stay.